Internal coupled-fed four-element multi-wideband diversity antenna for LTE mobile handsets - Singh H.S.; Pandey G.K.; Meshram M.K. (My University, 2025)
In this paper, a diversity antenna with four printed, folded, and shorted monopoles is presented. The each folded and shorted radiating elements are deposed at the four corners of printed circuit board and leaving the enough space for other mobile circuits. The proposed antenna covers LTE700/GSM850 (0.747 GHz - 0.895 GHz), GSM1800/1900/UMTS/IMT2100 (1.58 GHz - 2.2 GHz), Wi-Fi/Bluetooth/LTE2300 (2.37 GHz - 2.6 GHz), and LTE2500 (2.65 GHz - 2.7 GHz) frequency bands based on the -6dB reflection coefficient. The isolation between Ant. 1 and Ant. 2 is -4dB whereas other combinations (Ant.1 & Ant.3 and Ant.1. & Ant.4) provide isolation below -10dB. The better isolation is selected based on the adaptive selection of the best two elements out of four elements. Moreover, proposed four-element antenna array provides the pattern diversity for each combination of antenna elements which helps to mitigate the multipath fading effect. The S-parameters, radiation performances, and diversity performances are presented. © 2015 IEEE.